Maternal serum anti-Müllerian hormone at 11–13 weeks' gestation in the prediction of preeclampsia. (May 2015) - Birdir, Cahit; Fryze, Janina; Vasiliadis, Haralambos; Nicolaides, Kypros H.; Poon, Leona C.
Abstract Objective: To investigate the potential value of maternal serum anti-Müllerian hormone (AMH) at 11–13 weeks' gestation in the prediction of preeclampsia (PE). Methods: The serum concentration of AMH was measured at 11–13 weeks' gestation in cases of PE (n = 50) and normotensive controls (n = 150). Backward stepwise multiple regression analysis was used to determine which of the factors amongst the maternal characteristics and gestation were significant predictors of the serum AMH in the control group and from the regression model the value in each case and control was expressed as a multiple of the expected median (MoM). Results: In normotensive pregnancies, the maternal serum concentration of AMH is higher in Afro-Caribbean than in Caucasian women and in smokers than in non-smokers. In the PE group, the median serum concentration of AMH was significantly higher than in the controls (2.140 ng/L, IQR 1.968–2.273 versus 2.062 ng/L, IQR 1.938–2.181; p = 0.025), but the median MoM value of AMH was not significantly different between the PE group and the controls (1.040, IQR 0.941–1.081 versus 0.995, IQR 0.939–1.065, p = 0.147). Conclusions: Maternal serum AMH is not an effective early predictor for PE.